Examination under Anesthesia in Patients with Recurrent Patellar Dislocation: Prognostic Study - Fathalla, Ismail; Holton, James; Ashraf, Tanweer (The Journal of Knee Surgery, 2019)
Surgical management of patellar instability is a matter of wide debate. While some authors believe that isolated medial patellofemoral ligament (MPFL) reconstruction is sufficient, others advocate procedures to treat the underlying pathology, namely, patella alta and trochlear dysplasia. Radiological studies have been traditionally used as a determinant of these pathologies and to determine the need for an additional procedure. The value of examination under anesthesia (EUA) in formulating a treatment plan remains unknown. Our aim is to assess the prognostic value of EUA in assessing patients presenting for surgical treatment of recurrent patellar dislocations. We retrospectively reviewed the outcome after surgical treatment of 23 patients who had undergone isolated MPFL reconstruction for recurrent patella dislocation by a single surgeon in our tertiary center. All data were completed at the time of index surgery. Primary outcome was recurrent instability requiring revision surgery. The mean age of the 23 patients undergoing MPFL reconstruction was 17.4 years of age. The median trochlea tuberosity–trochlear groove (TT-TG) distance was 15 mm with a median Caton–Deschamps ratio of 1.3. Of the 23 patients who underwent MPFL reconstruction, 9 failed (39%). Median time to failure was 10.5 months. All patients who failed MPFL reconstruction had a dislocating patella on EUA at >30 degrees of flexion. Radiological assessment of the knee to assess its morphology is essential for preoperative surgical planning for patients with recurrent patellar instability. Cutoff values to determine the need for surgical procedures require a consistent method of imaging and are prone to flaws in measurement. However, we demonstrated that EUA provides valuable additional information toward an appropriate surgical approach.Based on our small cohort, we suggest that patients in whom patella remains dislocated past 30 degrees of knee flexion on EUA are unlikely to benefit from isolated MPFL reconstruction.
Keywords: MPFL; patellofemoral instability; trochleoplasty